Spotlight on adalimumab in the treatment of active moderate-to-severe hidradenitis suppurativa - Fotiadou C; Vakirlis E; Ioannides D (Dove Medical Press, 2016)
Christina Fotiadou, Efstratios Vakirlis, Dimitrios Ioannides First Department of Dermatology-Venereology, Aristotle University Medical School, Thessaloniki, Greece Abstract: Hidradenitis suppurativa (HS) is a chronic, recurrent, inflammatory skin disease that affects the hair follicles of the aprocrine gland-bearing anatomical areas of the body. It is characterized by deep painful nodules and abscesses that rupture and contribute to the formation of sinus tracks and scarring. The management of HS is based on the assessment of disease severity and a combination of medical and surgical treatment according to the European Guidelines. Adalimumab, a recombinant, fully humanized, anti-tumor necrosis factor alpha (anti-TNF-α) monoclonal antibody, is the only officially approved treatment for the management of moderate-to-severe HS. Case reports, concerning 42 patients who received adalimumab for severe HS (with the standard dose regimen for psoriasis), reported a cumulative response rate of 58% (≥50% in 23 patients) with a relapse rate of 71% (10 out of 14 patients). The most recent and most well-powered phase III, randomized placebo-controlled trials for the evaluation of the efficacy and safety of adalimumab in treatment of moderate-to-severe HS (PIONEER studies I and II) showed that the Hidradenitis Suppurativa Clinical Response (HiSCR) rate at week 12 was significantly higher for patients randomized to adalimumab compared to placebo. Adverse events were comparable to placebo. In conclusion, adalimumab, to date, holds the most robust data regarding treatment efficacy in HS. Larger, registry-based studies are needed to further establish the efficacy and safety profile of this anti-TNF-α agent in HS. Keywords: hidradenitis suppurativa, adalimumab, treatment